2020
DOI: 10.3329/bjm.v37i2.51209
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Noncritical Patients with Coronavirus Disease 2019 (COVID-19): Lessons from Bangladesh

Abstract: The scientific literatures on clinical manifestations of coronavirus disease 2019 (COVID-19) patients from South Asian countries including Bangladesh are limited. Documentation of clinical spectrum from various geographic locations is vital for future scientific studies and clinical management. This study is aimed to report the sociodemographic and clinical characteristics of noncritical patients with COVID-19 in Bangladesh. We conducted a cross-sectional study at three dedicated COVID-19 hospitals of Banglade… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
1
0
0
Order By: Relevance
“…The symptomatic pro le of the participants in this study corresponds to another study conducted among Bangladeshi patients and is also similar to ndings observed in China, Japan, Spain, Italy, and the USA as fever being the most common symptom whereas studies from Australia, the UK, Iceland, and a few other European countries showed cough as the most prevalent symptom [27,28]. A recent study showed that there is no signi cant association between the SARS-CoV-2 new variants and the symptoms, which indicates that the variation in symptoms across different geographic regions is likely due to outcomes of complex host-pathogen interactions [29].…”
Section: Discussionsupporting
confidence: 89%
“…The symptomatic pro le of the participants in this study corresponds to another study conducted among Bangladeshi patients and is also similar to ndings observed in China, Japan, Spain, Italy, and the USA as fever being the most common symptom whereas studies from Australia, the UK, Iceland, and a few other European countries showed cough as the most prevalent symptom [27,28]. A recent study showed that there is no signi cant association between the SARS-CoV-2 new variants and the symptoms, which indicates that the variation in symptoms across different geographic regions is likely due to outcomes of complex host-pathogen interactions [29].…”
Section: Discussionsupporting
confidence: 89%
“…In Bangladesh, there is limited information regarding the clinical characteristics of hospitalized COVID-19 patients who die or survive. 12,13 It is necessary to identify factors that are predictive of mortality in this setting. Therefore, this study was conducted at Dhaka Medical College Hospital to determine the demographic profile, clinical presentation, and laboratory parameters of COVID-19 patients admitted to this center who died or were discharged alive to determine the predictors of mortality.…”
Section: Introductionmentioning
confidence: 99%